Representation of Inner Family Communication Film, Semiotic Analysis John Fiske: Reperesentasi Komunikasi Keluarga dalam Film, Analisis Semiotika John Fiske - Maulana, Dandy; Aesthetika, Nur Maghfirah (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the representation of family communication in the film